1994
DOI: 10.1093/genetics/136.3.731
|View full text |Cite
|
Sign up to set email alerts
|

Complex frameshift mutations mediated by plasmid pKM101: mutational mechanisms deduced from 4-aminobiphenyl-induced mutation spectra in Salmonella.

Abstract: We used colony probe hybridization and polymerase chain reaction/DNA sequence analysis to determine the mutations in approximately 2,400 4-aminobiphenyl (4-AB) +S9-induced revertants of the -1 frameshift allele hisD3052 and of the base-substitution allele hisG46 of Salmonella typhimurium. Most of the mutations occurred at sites containing guanine, which is the primary base at which 4-AB forms DNA adducts. A hotspot mutation involving the deletion of a CG or GC within the sequence CGCGCGCG accounted for 100 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…The ability to generate one-base and twobase deletions was shown to depend on three factors: (a) the nature of the base inserted opposite the adduct, (b) the sequence context of the adduct, and (c) the overall rate of translesion DNA synthesis past the adduct. A similar mechanism was also proposed from 4-aminobiphenyl-and 2-amino-6-methyldipyrido[1,2-a:3′,2′-d]imidazole-induced mutation spectra in Salmonella (18,19).…”
supporting
confidence: 60%
“…The ability to generate one-base and twobase deletions was shown to depend on three factors: (a) the nature of the base inserted opposite the adduct, (b) the sequence context of the adduct, and (c) the overall rate of translesion DNA synthesis past the adduct. A similar mechanism was also proposed from 4-aminobiphenyl-and 2-amino-6-methyldipyrido[1,2-a:3′,2′-d]imidazole-induced mutation spectra in Salmonella (18,19).…”
supporting
confidence: 60%
“…It is notable that the mutation specificity observed with MX and CMCF in the hisG46 allele is identical to that of benzo-[a]pyrene, 4-aminobiphenyl, and 2-amino-6-methyldipyrido[1,2-a:3,2-d]imidazole. These compounds induce large bulky DNA adducts that block replication (23,25,38,52) which leads to base substitutions according to the "adenine rule" (53). The fact that MX and CMCF cause this type of mutation suggests that they produce adducts which are blocks to replication and necessitate a replication mechanism that is typified by the adenine rule.…”
Section: Discussionmentioning
confidence: 99%
“…DNA Colony Hybridization. The purified revertants of strains carrying the hisG46 allele (TA1535, TA1950; TA100) were analyzed by the colony hybridization procedure initially described by Cebula and Koch () with 15-nucleotide oligomers with slight modifications (see also refs and ): The filters were hybridized for 24 h at 37 °C; then CAC, CTC, and CCC were washed in 3x SSC (saline sodium citrate) at 47 °C for 30 min, TCC at 47 °C for 60 min, ACC at 50 °C for 30, and GCC at 55 °C for 35 min. Recently, it has been shown that mutants that hybridize to the probe with the initial CCC sequence contain a supressor mutation in the anticodon region of either of two tRNA Thr genes and represent TA → GC transversions ().…”
Section: Methodsmentioning
confidence: 99%
“…The important role of PAHs, aromatic amines, nitro-PAHs, and so forth, in the mutagenicity and carcinogenicity of air and combustion emissions is reflected in the mutation spectra, that is, the types of mutations, induced by such complex mixtures in the base-substitution strain TA100 of Salmonella. Thus, G to T is the predominant base substitution induced in the presence of S9 by PM from air and its base/ neutral fraction (DeMarini et al, 1994b) F I G U R E 9 Correlation between mutagenicity and PAH emission factors for (a) agricultural (polyethylene) plastic and kerosene burned in a rotary kiln (Linak et al, 1989), (b) simulated biomass burning (Kim et al, 2018), and (c) cookstoves (Champion et al, 2020;Mutlu et al, 2016); data from Tables 1 and 2 mutation than does the PAH B[a]P or the aromatic amine 4aminobiphenyl (DeMarini, 2000;DeMarini et al, 1996;Kucab et al, 2019;Levine et al, 1994).…”
Section: Mutation Spectra Of Organics From Air and Combustion Emissionsmentioning
confidence: 99%
“…The G to A, G to C, and G to T mutations noted above reflect the types of mutations induced by various types of nitro‐PAHs, which are direct‐acting mutagens in these emissions (DeMarini et al, 1996). Nitro‐PAHs induce more of these classes of mutation than does the PAH B[ a ]P or the aromatic amine 4‐aminobiphenyl (DeMarini, 2000; DeMarini et al, 1996; Kucab et al, 2019; Levine et al, 1994).…”
Section: Mutation Spectra Of Organics From Air and Combustion Emissionsmentioning
confidence: 99%